Enhancing Critical Thinking in Elementary Students Through the Development Students Worksheet Using a Discovery Learning Approach - Siska Tresia Oktari; Ardipal Ardipal (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study aimed to develop and evaluate Discovery Learning-based Student Worksheets (SW) to enhance critical thinking skills at the elementary school level. Addressing the need for innovative tools in education, the research assessed the validity, practicality, and effectiveness of these worksheets in improving student outcomes. A Research and Development (RD) approach using the 4D model—definition, design, development, and deployment—was employed. The study was conducted in three elementary schools in West Sumatra. Data were collected through observation sheets, interview questionnaires, validation instruments, practicality questionnaires, and evaluation tests. The validity test of the SW yielded an average score of 89% (very valid), with media and material validity rated at 90% and 80%, respectively. Practicality tests showed an average score of 88.5% (very practical), based on teacher and student responses of 87% and 90%. Critical thinking test instruments demonstrated high validity, reliability, and appropriate levels of difficulty and discrimination. Implementation in two schools resulted in significant improvements in student outcomes, with an average N-Gain score of 0.74 (74.09%), indicating substantial enhancement in critical thinking skills. The findings highlight the SW's potential as an effective tool for fostering critical thinking at the elementary level. The results suggest that integrating Discovery Learning principles can significantly improve learning outcomes. The Discovery Learning-based SW was proven valid, practical, and effective. Future research should explore its application in diverse educational contexts and examine long-term impacts on critical thinking development.